15N natural abundance of vehicular exhaust ammonia, quantified by active sampling techniques. (15th June 2021) - Song, Linlin; Walters, Wendell W.; Pan, Yuepeng; Li, Zhengjie; Gu, Mengna; Duan, Yihang; Lü, Xuemei; Fang, Yunting
Abstract: Vehicular exhaust has been identified as an important ammonia (NH3 ) emission source in urban areas using the stable isotope tracer technique (δ 15 N); however, its δ 15 N signature remains poorly constrained due to difficulties in concentrating and speciating NHx (NH3  + particulate NH4 + ). In this study, we deployed two active sampling techniques, MCIs (Multi-nozzle Cascade Impactor sampler; "particle-gas" order) and CCSCs (ChemComb Speciation Cartridge sampler; "gas-particle" order), to collect vehicular exhaust NHx in a long urban tunnel in Shenyang, China, and quantified the 15 N from the collected NH3 and NH4 + . While no significant difference in tunnel NH3 concentrations between the two samplers was observed (n = 21), the δ 15 N-NH3 was slightly higher using the MCIs (6.3 ± 1.6‰) compared to the CCSCs (4.8 ± 2.3‰) during the tunnel operation period. This minor absolute difference of 1.5 ± 2.8‰ may derive from denuder-saturation used within the CCSCs that lead to NHx speciation ambiguity, which also caused significant δ 15 N-pNH4 + differences between the two sampling approaches. Our results suggest that both active samplers can well characterize the δ 15 N-NHx in the ambient environment, but the "particle - gas" sampling approach performs better in elevated NH3 concentration environments. We recommend that the δ 15 N value of 6.3‰ is used as the isotope end member for vehicle NH3 when performing NH3 source apportionment. Graphical abstract: Image 1 Highlights: Two types of active samplers were used to collect vehicular exhaust NHx in urban tunnel. Minor δ 15 N–NH3 difference (~1.5‰) was observed between two types of active samplers. The "particle - gas" sampling type may perform better in high NH3 environments. A value of 6.3‰ is recommended as the δ 15 N signatures of vehicle NH3 for source apportionment.